ESTIMATING THE PREMIUM FOR TITLED AGRICULTURAL LAND IN UGANDA - ALOBO , SARAH; BASHAASHA , BERNARD; JOHNNY , MUGISHA (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
The study investigates the value for titled agricultural land in Uganda using data on 9,045 parcels of land from the 2005/2006 Uganda National Household Survey. Data were analyzed using regression techniques. The results showed a positively significant premium for leasehold title as opposed to other forms of titled agricultural land in Uganda; that traditional determinants of land value such as current use, soil quality, presence of perennials and proximity to the homestead are not significant for agricultural land in Uganda; and that per hectare price of agricultural land in peri-urban locations was significantly higher than in rural areas by about Ushs 1.7 million. There is also an overlap in land ownership rights for mailo land where two people have claims to the same piece of land, the mailo title holder and the kibanja tenant. It was concluded that the current land policy should promote the leasehold system in peri-urban areas, since this type of tenure opens land to a wide range of users and use-options. The land policy also needs to address the double ownership structure under the mailo tenure which constrains its marketability and transferability.